MalayA: The conscious club: Terminal year end report - Alejandro, Samantha Therese P. (Animo Repository, 2022)
MalayA The Conscious Club is a sustainable fashion brand established in December 2021, and the main purpose of this clothing line is to address societal and environmental issues through business solutions. MalayA The Conscious Club started out as a practicum business by 5 Entrepreneurship students. The main purpose of MalayA clothing is to promote slow fashion, to provide multiple ways of wearing a piece of clothing, and to make sustainable fashion accessible to Filipinos. MalayA wants to uphold a sustainable fashion brand with designs that are classic, timeless, and multi-functional so that consumers will buy fewer clothes and have more opportunities to explore and give a space for self-expression around that one item. The company also aims to address some societal and environmental issues through business solutions, which is one of the main reasons why the business was built. From the utilization of materials, giving livelihood opportunities to the local weavers to feature their weaves, and lastly, giving awareness to the consumers about textile waste and how to live sustainably. The first collection of Malaya features the MULI line. One set includes a tube and a pair of detachable sleeves and a pair of adjustable and detachable straps. It is designed to last the users from their teen years to their adulthood. Consumers can choose from three different styles of top, namely, Amihan, Dalisay and Mahalia. The Amihan top is made from soft linen and is garterized and flowy. The Dalisay top is made from soft linen and features a fold on the front, a garter on the back and is flowy. The Mahalia top is made from premium linen and is stretchy and form fitting with a smocked portion on the back. The Dalisay and Amihan tops is be available in Extra Small to Small (XS-S), Medium to Large (M-L) sizes. The Mahalia tops is be available in Small (S), Medium (M), and Large (L) sizes. Some of the colors offered are Sage, Charcoal, Lavender, Cream and Off White colors. The Mahalia top is also available in the Binakul weave. The puff sleeves and straps is be made in linen or the Binakul weave. The next collection is the Haraya top. Haraya is a 4-in-1 multiway top that can be worn inside out and back to back. It has a V neckline on the first side and a straight one on the other. The Haraya tops are available in Extra Small to Small (XS-S), Small to Medium (S-M), Medium to Large (M-L), and Extra Large to Extra Extra Large (XL-XXL) sizes.